24. Season three [videorecording (DVD)] - Sutherland, Kiefer, 1966-; Wynter, Sarah, 1973-; Cuthbert, Elisha (Twentieth Century Fox Home Entertainment, 2004)
"It's been three years since CTU agent, Jack Bauer thwarted a terrorist attempt to plunge the United States into war. Now he's back in L.A. after working undercover for six months bringing down drug lord Ramon Salazar. But then the FBI receives a phone call threatening the release of a deadly virus in Los Angeles if Salazar isn't released from prison within six hours. As CTU races to locate the virus, Jack realizes that the only way to prevent additional terrorist demands is to find the source of the virus-- by breaking Salazar out of prison himself."--Container.